2000
DOI: 10.1046/j.1525-1314.2000.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Hornblende geothermometry of amphibolite layers of the Popple Hill gneiss, north‐west Adirondack Lowlands, New York, USA

Abstract: The exchange reaction tschermakite+2 diopside+2 quartz=tremolite+2 anorthite (HPCQ), in combination with the thermodynamic database TWQ (version 1.02, Berman, 1991), has been evaluated for its usefulness as a geothermometer. This reaction, which is both water conserving (independent of water fugacity) and which does not require the presence of garnet, is well suited for studying pyroxene‐bearing amphibolites. As an application of this geothermometer, we have re‐examined the amphibolites occurring in the Popple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Liogys and Jenkins (2000), among others, have shown that this area reached metamorphic temperatures as high as 760°C. The PbSL age is therefore not directly comparable to existing ages from the main parts of the Lowlands where maximum temperatures were in the order of 650 to 700°C (section 2.1).…”
Section: Northeast Adirondack Lowlands (Um-p)mentioning
confidence: 73%
See 2 more Smart Citations
“…Liogys and Jenkins (2000), among others, have shown that this area reached metamorphic temperatures as high as 760°C. The PbSL age is therefore not directly comparable to existing ages from the main parts of the Lowlands where maximum temperatures were in the order of 650 to 700°C (section 2.1).…”
Section: Northeast Adirondack Lowlands (Um-p)mentioning
confidence: 73%
“…Peak metamorphism conditions in the Lowlands reached amphibolite facies under low H 2 O activity with pressures close to 7 kbar and temperatures around 650 to 700°C (Kitchen and Valley, 1995;Liogys and Jenkins, 2000). Higher temperatures were reached near the Carthage-Colton zone (760°C; Liogys and Jenkins, 2000), and in the southeastern areas of the Lowlands due to contact metamorphism induced by the 1153 Ma intrusion of the Diana syenite (ϳ900°C; Powers and Bohlen, 1985).…”
Section: Lower Marble and Upper Marble Adirondack Lowlands Grenvillmentioning
confidence: 99%
See 1 more Smart Citation
“…Background, scale factor, cell dimensions and Lorentzian coefficients ‘LX’ (particle size) were refined. Although the reported uncertainties (precision) for phase abundances in Rietveld refinements are very low (<1 wt%), the observed accuracy in weight percentages of minerals as calculated for mixtures of natural minerals by Liogys and Jenkins (2000) could deviate 3–4 wt% on average from that of the known proportions. The uncertainties for the synthetic mineral mixtures in this study are smaller (1–3 wt% as shown in Table 4) since they usually do not have such high preferred orientations as natural minerals.…”
Section: Experimental Methodsmentioning
confidence: 93%